Soil Aquifer Treatment of Municipal Sewage under Layered Soil Columns - Hardaha, M. K. (Journal of Agricultural Engineering, 2014)
A laboratory study was carried out on 18 columns of different soil layers to evaluate the effect of soil layers on soil aquifer treatment system for treatment of municipal wastewater. Six columns with layers of clay loam and loamy sand soils (top layer - 30, 45 and 60 cm of clay loam, 30 cm of clay loam amended with 15% sand, 30 cm of clay loam amended 30% sand and one homogeneous loamy sand) were loaded with municipal sewage continuously for two weeks. Treated water collected from the bottom of the column and raw sewage was analyzed for its constituents in terms of pH, EC, BOD5, COD, turbidity, total solids, dissolved solids, calcium, magnesium, chloride, carbonate, nitrogen, phosphorus, sodium, potassium, metals (iron, zinc, copper, manganese) and total coliform counts. The overall quality of sewage improved by soil aquifer treatment as the parameters found in treated water was well within irrigation standard. Columns having clay loam layer of 450 mm and 600 mm were superior to other columns.